2015
DOI: 10.1063/1.4932349
|View full text |Cite
|
Sign up to set email alerts
|

Graded-index magnonics

Abstract: The wave solutions of the Landau-Lifshitz equation (spin waves) are characterized by some of the most complex and peculiar dispersion relations among all waves. For example, the spin-wave ("magnonic") dispersion can range from the parabolic law (typical for a quantum-mechanical electron) at short wavelengths to the nonanalytical linear type (typical for light and acoustic phonons) at long wavelengths. Moreover, the longwavelength magnonic dispersion has a gap and is inherently anisotropic, being naturally nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 86 publications
0
41
0
Order By: Relevance
“…Furthermore, recent experimental studies showed an efficient spin-wave electrical tuning in thin magnetic films, such as YIG (Y 3 Fe 5 O 12 ) [4]. At present, interest to such phenomena is very active due to their potential applications in magnon spintronics and magnonics [7][8][9], where an electrically controlled phase shifter for spin waves could become an essential component of spin-wave devices. Nonreciprocity and unidirectionality of spin-wave propagation would be also valuable for this purpose [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent experimental studies showed an efficient spin-wave electrical tuning in thin magnetic films, such as YIG (Y 3 Fe 5 O 12 ) [4]. At present, interest to such phenomena is very active due to their potential applications in magnon spintronics and magnonics [7][8][9], where an electrically controlled phase shifter for spin waves could become an essential component of spin-wave devices. Nonreciprocity and unidirectionality of spin-wave propagation would be also valuable for this purpose [10].…”
Section: Introductionmentioning
confidence: 99%
“…[10,31] where the domain wall oscillations at frequency ω were observed to emit spin waves at twice the frequency, i.e., 2ω. Our theory suggests that the spin wave emission from domain walls, at a frequency equal to that of the driving magnetic field [12,13] or spin-polarized current [14] should rather be interpreted as a linear excitation due to the magnetic inhomogeneity [32] ("graded magnonic index" [20]) created by the domain wall, when excited by a uniform magnetic field.…”
mentioning
confidence: 99%
“…This potential is mostly known for its peculiar property of 100% transmission of incident waves at any frequency, for certain parameters of the potential [19]. While forming such a potential in other systems is difficult, serendipitously the reflectionless Pöschl-Teller potential exactly describes the graded magnonic index profile [20] due to a Bloch domain wall, allowing the peculiar behavior to be both investigated and exploited in magnetic systems [21]. Furthermore, when the domain wall is driven by a uniform microwave magnetic field, the Pöschl-Teller profile happens to be present not only as the potential, but also as a driving term in the obtained Schrödinger-like equation.…”
mentioning
confidence: 99%
“…Other methods of modifying the dispersion include the magnonic crystals employing magnetic superlattices [1,14], and the gradient-index magnonics employing non-uniform effective magnetic field configurations [15,16].…”
mentioning
confidence: 99%